Assessment of Serum Adiponectin and Leptin in Chronic Periodontitis Over Healthy Individuals - Reghunathan S. Preethanath; Swaroop Chandy; Nubesh Khan Syed; Bugude Shiva Shankar; Pavithra Rangarajan Seshadri; R Narayane; P. K. Saraswathi Bai (Journal of Pharmacy and Bioallied Sciences)
Objective: The objective of the research was to ascertain whether serum levels of the biochemical markers adiponectin and leptin are related to clinical periodontal characteristics. Materials and Method: For the study, 20 people with chronic periodontitis (Group A) and 20 healthy people (Group B) were enrolled. Assessments were conducted on periodontal markers, including bleeding on probing (POP), gingival index (GI), plaque index (PI), probing pocket depth (PPD), and clinical attachment level (CAL). An enzyme-linked immunosorbent assay (ELISA) test was used to assess the levels of adiponectin and leptin in serum samples. Result: There was significant elevation in average level of leptin in chronic periodontitis in association to that in healthy group. On the other hand, there was considerable decrease in serum adiponectin in group A in association to healthy group. The ratio of leptin\adiponectin was appreciably greater amongst periodontitis group compared to healthy group. Conclusion: The current investigation leads us to the conclusion that the pathophysiology of periodontitis is significantly influenced by serum levels of adiponectin and leptin.